2005
DOI: 10.1021/jo050105q
|View full text |Cite
|
Sign up to set email alerts
|

Single and Double Suzuki−Miyaura Couplings with Symmetric Dihalobenzenes

Abstract: [reaction: see text] m- or p-Diiodobenzene undergoes selective double coupling reactions with arylboronic acids and esters. Selectivity for double coupling over single coupling is remarkably strong: even with a diiodobenzene:monoboronic acid ratio of 10:1, the products of double coupling are formed in good yields. Steric hindrance and electronic influences of the boronic acid or ester, and reaction conditions do not appear to impact significantly upon the outcome of the reaction. In contrast, m- and p-dibromob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(41 citation statements)
references
References 18 publications
1
39
1
Order By: Relevance
“…Particularly appealing is the synthesis of the biphenyl core by a Suzuki-Miyaura coupling as suitably functionalized phenyl precursors were already available. [41] As displayed in Scheme 2, 1-(4-iodophenyl)piperidine and 4,4,5,5-tetramethyl-2-(4-nitrophenyl)-1,3,2-dioxaborolane were treated with a palladium catalyst and a base in a refluxing toluene/methanol mixture to provide the desired NLO model compound 1a in 26 % yield after column chromatography (CC). Promising preliminary optical investigations of 1a motivated the development of a general synthetic route to make the entire series of NLO model compounds available.…”
Section: Synthesismentioning
confidence: 99%
“…Particularly appealing is the synthesis of the biphenyl core by a Suzuki-Miyaura coupling as suitably functionalized phenyl precursors were already available. [41] As displayed in Scheme 2, 1-(4-iodophenyl)piperidine and 4,4,5,5-tetramethyl-2-(4-nitrophenyl)-1,3,2-dioxaborolane were treated with a palladium catalyst and a base in a refluxing toluene/methanol mixture to provide the desired NLO model compound 1a in 26 % yield after column chromatography (CC). Promising preliminary optical investigations of 1a motivated the development of a general synthetic route to make the entire series of NLO model compounds available.…”
Section: Synthesismentioning
confidence: 99%
“…[44][45][46] There have been several reports of model reactions for chain-growth Suzuki-Miyaura coupling polymerization, [47][48][49] but the chain-growth condensation polymerization had not been demonstrated yet. Furthermore, in chain-growth Suzuki-Miyaura coupling polymerization, stable arylpalladium(II) halide complex could be used as an externally added initiator, and the aryl group of the complex would serve as an initiator unit of the polymer.…”
Section: Catalyst-transfer Condensation Polymerization Via Suzuki-miymentioning
confidence: 99%
“…However, a significant number of selective single couplings with di-or tri-haloaromatics have also been reported. 19 In these cases, to encourage single coupling products, a low molar ratio of boronic acid to polyhalobenzenes is employed. However, contradictory to this, it has also been reported that during the selective double coupling of arylboronic acids and esters with symmetrical p-dihalobenzene this molar ratio does not affect the selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Even when the ratio is 10/1 the products of double coupling are preferentially obtained. 19 Halogen has also been identified as one of the major factors in determining selectivity, with p-dibromobenzene resulting in single couplings with arylboronic acids with high selectivity, while p-diiodobenzene results in double-coupled products. 19 To the best of our knowledge, no study on the selectivity of the p-dihalobiphenyl and p-dihalo(oligo-p-phenylenes) reaction has been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation